Islamic Leadership in Managing Pesantren: A Case Study of Darul Falah Arroudloh in the Industrial Revolution 5.0 Era - Angga Yoga Pratama (MANAGIERE: Journal of Islamic Educational Management, 2025)
This study explores the kyai’s leadership in managing Pondok Pesantren Darul Falah Arroudloh, Jember, within the context of the Industrial Revolution 5.0 era. Using a descriptive qualitative case study, data were gathered through observation, interviews, and documentation involving three key informants: the caretaker, the head of the pesantren, and a student. The data were analyzed using Miles and Huberman’s interactive model with triangulation to ensure validity. The findings indicate that the kyai’s leadership is pivotal—not only as an educator and moral guide but also as a role model, motivator, and ultimate decision-maker. The kyai effectively integrates traditional Islamic scholarship with digital innovations such as online lectures, virtual Quran recitations, and digital attendance systems. This leadership embodies religious, humanistic, and adaptive values in addressing modern challenges. However, the study’s limitation lies in its narrow scope and small sample, suggesting the need for comparative research across multiple pesantren. Penelitian ini mengkaji kepemimpinan kyai dalam mengelola Pondok Pesantren Darul Falah Arroudloh, Jember, pada era Revolusi Industri 5.0. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan jenis studi kasus. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi dengan tiga informan utama: pengasuh, kepala pesantren, dan seorang santri. Analisis data dilakukan menggunakan model interaktif Miles dan Huberman dengan triangulasi sumber dan metode untuk menjaga keabsahan. Hasil penelitian menunjukkan bahwa kepemimpinan kyai berperan sentral, tidak hanya sebagai pendidik dan pembimbing moral, tetapi juga sebagai teladan, motivator, dan pengambil keputusan utama. Kyai berhasil mengintegrasikan tradisi keilmuan Islam berbasis kitab klasik dengan inovasi digital, seperti pengajian daring, tadarus virtual, dan sistem absensi digital. Kepemimpinan tersebut mencerminkan nilai-nilai religius, humanis, dan adaptif dalam menghadapi tantangan modern. Keterbatasan penelitian ini terletak pada jumlah informan dan fokus yang sempit, sehingga disarankan penelitian komparatif di beberapa pesantren.